2004
DOI: 10.1002/mar.20012
|View full text |Cite
|
Sign up to set email alerts
|

When will larger‐sized female models in advertisements be viewed positively? The moderating effects of instructional frame, gender, and need for cognition

Abstract: A variety of negative consequences for girls and women have been associated with women's and men's viewing unrealistic portrayals of women in advertising. However, research on the positive consequences of presenting larger-sized women in advertisements, and the conditions under which they are effective, has been lacking. The present research examined such positive effects and found that larger-sized female models in ads were rated as more attractive when an instructional frame activated nontraditional beliefs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 36 publications
1
44
1
2
Order By: Relevance
“…Guidelines in the pretest followed the procedure as suggested by Martin, Veer, and Pervan (2007), Peck and Loken (2004) and Smeesters and Mandel (2006). In particular, one-half of the students examined the moderately fat models of both Western and Chinese backgrounds while the other group examined the moderately thin models.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Guidelines in the pretest followed the procedure as suggested by Martin, Veer, and Pervan (2007), Peck and Loken (2004) and Smeesters and Mandel (2006). In particular, one-half of the students examined the moderately fat models of both Western and Chinese backgrounds while the other group examined the moderately thin models.…”
Section: Methodsmentioning
confidence: 99%
“…Peck and Loken (2004) showed that in the right context, for example, a new women's magazine with larger models, with a body shape that is congruent with an obtainable body shape, will be viewed as being more attractive and should not have a negative impact on body image. On the other hand, women with larger body shapes may make more of a comparison with an obtainable body shape, and feel they ought to be able to meet this ideal, as opposed to a much thinner body shape.…”
Section: H3bmentioning
confidence: 97%
See 2 more Smart Citations
“…First, most research (e.g., Groesz et al, 2002;Henderson-King & Henderson-King, 1997;Myers & Biocca, 1992;Peck & Loken, 2004;Richins, 1991;Smeesters & Mandel, 2006;Wilcox & Laird, 2000) has focused on the effect of exposing women to slim or regular-size models on their self-image. No research to date has investigated if women actually prefer regular-size models to slim ones, and if so, which women.…”
Section: Journal Of Euromarketingmentioning
confidence: 99%